Sticta flakusiorum and S. kukwae—two additional new species from the Neotropics (Peltigerales, Peltigeraceae) - Emilia Anna Ossowska; Bibiana Moncada; Robert Lücking; Emmanuel Sérusiaux; Nicolas Magain (MycoKeys)
Two additional species of Sticta are described as new to science based on material from Bolivia and Peru and supported by phylogenetic analysis of the fungal ITS barcoding marker. The two new species represent lineages within clade I on the global Sticta phylogeny. Sticta flakusiorum Ossowska, B. Moncada & Lücking is a species in the S. humboldtii morphodeme and is characterized by lobes partly to entirely covered with white hairs, also covering the margins of submarginal and laminal apothecia, and the scabrid basal membrane of cyphellae, which is white to yellow, or partly brown, and when yellow K+ purple. The taxon was discovered at a single locality in Bolivia, but it is closely related to a potentially new Sticta species from Peru, which is here left undescribed. The other new species, S. kukwae Ossowska, Magain & Sérus., belongs to the S. weigelii morphodeme. It has lobes with sinuous margins and dark, palmate to corymbose phyllidia. It was collected at several locations in Peru and a single locality in Bolivia.